Larvae of an invasive scarab increase greenhouse gas emissions from soils and recruit gut mycobiota involved in C and N transformations - Avila-Arias, Helena; Turco, Ronald F.; Scharf, Michael E.; Groves, Russell L.; Richmond, Douglas S. (Frontiers in Microbiology, 2023)
Soil-derived prokaryotic gut communities of the Japanese beetle Popillia japonica Newman (JB) larval gut include heterotrophic, ammonia-oxidizing, and methanogenic microbes potentially capable of promoting greenhouse gas (GHG) emissions. However, no research has directly explored GHG emissions or the eukaryotic microbiota associated with the larval gut of this invasive species. In particular, fungi are frequently associated with the insect gut where they produce digestive enzymes and aid in nutrient acquisition. Using a series of field and laboratory experiments we (1) assessed the impact of JB larvae on soil GHG emissions; (2) characterized gut mycobiota associated with these larvae; and (3) examined how soil biological and physicochemical characteristics influence variation in both GHG emissions and the composition of larval gut mycobiota. In laboratory trials, emission rates of CO2, CH4, and N2O from infested soil were ≥ 6.3 higher per larva than emissions from JB larvae alone whereas CO2 emission rates from soils previously infested by JB larvae were 1.3 higher than emissions from JB larvae alone. In the field, JB larval density was a significant predictor of CO2 emissions from infested soils, and both CO2 and CH4 emissions were higher in previously infested soils. We found that geographic location had the greatest influence on variation in larval gut mycobiota, although the effects of compartment (i.e., soil, midgut and hindgut) were also significant. There was substantial overlap in the composition and prevalence of the core fungal mycobiota across compartments with prominent fungal taxa being associated with cellulose degradation and prokaryotic methane production/consumption. Soil physicochemical characteristics such as organic matter, cation exchange capacity, sand, and water holding capacity, were also correlated with both soil GHG emission, and fungal -diversity within the JB larval gut. Results indicate JB larvae promote GHG emissions from the soil directly through metabolic activities, and indirectly by creating soil conditions that favor associated microbial activity. Fungal communities associated with the JB larval gut are primarily influenced by adaptation to local soils, with many prominent members of that consortium potentially contributing to C and N transformations capable of influencing GHG emissions from infested soil.